Worth the Wait: Delayed Recall after 1 Week Predicts Cognitive and Medial Temporal Lobe Trajectories in Older Adults - Lindbergh, Cutter A. (J Int Neuropsychol Soc, 2020)
OBJECTIVE: We evaluated whether memory recall following an extended (1 week) delay predicts cognitive and brain structural trajectories in older adults. METHOD: Clinically normal older adults (52–92 years old) were followed longitudinally for up to 8 years after completing a memory paradigm at baseline [Story Recall Test (SRT)] that assessed delayed recall at 30 minutes and 1 week. Subsets of the cohort underwent neuroimaging (N = 134, mean age = 75) and neuropsychological testing (Ns = 178–207, mean ages = 74–76) at annual study visits occurring approximately 15–18 months apart. Mixed-effects regression models evaluated if baseline SRT performance predicted longitudinal changes in gray matter volumes and cognitive composite scores, controlling for demographics. RESULTS: Worse SRT 1-week recall was associated with more precipitous rates of longitudinal decline in medial temporal lobe volumes (p = .037), episodic memory (p = .003), and executive functioning (p = .011), but not occipital lobe or total gray matter volumes (demonstrating neuroanatomical specificity; ps > .58). By contrast, SRT 30-minute recall was only associated with longitudinal decline in executive functioning (p = .044). CONCLUSIONS: Memory paradigms that capture longer-term recall may be particularly sensitive to age-related medial temporal lobe changes and neurodegenerative disease trajectories.